ANALISIS PEMBUBARAN ORGANISASI KEMASYRAKATAN BERDASARKAN UNDANG UNDANG NOMOR 16 TAHUN 2017 PERSPEKTIF SIYASAH DUSTURIYAH - Alfin Maqbul Fauzi; Idzam Fautanu; Lutfi Fahrul Rizal (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the mechanism for disbanding community organizations based on Law Number 16 of 2017. The dissolution regulated in the mass organization law also contradicts the theory of the rule of law and justice in the civil service. The implementation of just law is fundamental to creating a peaceful cycle of society and maintaining the rights of freedom of the community, especially in association and assembly. This study uses a normative legal method. The results of this study indicate that the government should continue to pay attention to the rights of the community in freedom of assembly and association and continue to implement due process of law as a representation of efforts to create a just government to present a more peaceful democratic climate in addition to the state's anticipation of organizations that conflict with Pancasila and the 1945 Constitution.